The Effect of Nature of Science (NoS) Explicit Learning Design on Students’ NoS Comprehension at Elementary School - Cucun Sutinah; Ari Widodo (UIN Siber Syekh Nurjati Cirebon, 2020)
AbstractThis research aims to investigate the effect of Nature of Science (NoS) learning design implementation on students’ NoS comprehension. The research employed the pre-experimental method with one group of pretest and post-test design. The samples, selected by purposive sampling technique, were 34 fifth grade students at one public school in Bandung city. A Likert-scale questionnaire was used as the instrument for collecting the data. The data analysis employed a descriptive quantitative technique by independent sample t-tests with the assistance of SPSS and Microsoft Excel tools. The findings show that there was a significant increase from the scores in pretest and post-test as the significance score is 0.000 < α = 0.05. The average score in the post-test was higher than the score in the pretest, indicating that student’s NoS understanding improved. In terms of percentage, NoS comprehension aspects increased from 13% to 78%, then 91%. The aspect with the highest increase was creativity (100%), whereas the aspect with the lowest increase was the socio and cultural embeddedness, with 87% increase. This research suggests that the implementation of the Nature of Science (NoS) explicit learning design has a significant effect on the students’ NoS comprehension.Keywords: learning design, nature of science, students’ NoS comprehension.AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh implementasi desain pembelajaran Nature of Science (NoS) terhadap pemahaman NoS siswa. Metode yang digunakan dalam penelitian ini adalah metode pra-eksperimen dengan one group pretest and posttest only design. Sampel diambil dengan teknik purposive sampling, yaitu sebanyak 34 siswa kelas V di salah satu sekolah negeri di kota Bandung. Kuesioner skala likert digunakan sebagai instrumen untuk mengumpulkan data. Analisis data menggunakan teknik deskriptif kuantitatif dengan uji independent sample t-tests berbantuan SPSS dan Microsoft Excel. Hasil penelitian menunjukkan bahwa terdapat peningkatan yang signifikan dari nilai pretest dan post-test, di mana nilai signifikansinya sebesar 0,000 <α = 0,05. Nilai rata-rata post-test lebih tinggi dari pada nilai pretest, yang menunjukkan bahwa pemahaman NoS siswa meningkat. Dari segi persentase, aspek pemahaman NoS meningkat dari 13% menjadi 78%, kemudian 91%. Aspek yang mengalami peningkatan tertinggi adalah kreativitas (100%), sedangkan aspek yang mengalami peningkatan terendah adalah keterikatan sosial dan budaya, yaitu sebesar 87%. Penelitian ini menunjukkan bahwa penerapan desain pembelajaran eksplisit Nature of Science (NoS) memiliki pengaruh yang signifikan terhadap pemahaman NoS siswa.Kata kunci: desain pembelajaran, nature of science, pemahaman NoS siswa.